Screening of coumarin derivatives as a potential Alzheimer’s Disease treatment drugs on Drosophila melanogaster - Nurul Akmar Hussin; Abdul Ashraf Rasid; Min, Ooi Hui; Ghows Azzam; Mardani Abdul Halim (Biotechnology Research Institute, UMS, 2024)
Alzheimer's disease (AD) stands as the most prevalent form of neurodegenerative ailment worldwide, characterized by the accumulation of amyloid beta (Aβ) plaques. Unfortunately, there is currently no effective cure for this condition. To investigate potential treatment options, researchers have turned to Drosophila melanogaster as an ideal animal model for studying AD. In this context, coumarin, a naturally occurring phytochemical initially discovered in tonka bean, and its derivatives have garnered significant attention for their diverse beneficial biological properties. The present study aimed to explore the efficacy of coumarin derivatives in mitigating the adverse effects of Aβ aggregation. Using the Drosophila model expressing human Aβ42, researchers observed a rough eye phenotype (REP) and decreased lifespan. To evaluate the neuroprotective effects of coumarin derivatives, the treated groups' eye morphology was compared with both positive and negative control groups. Encouragingly, the group treated with S5-44 exhibited the most favourable eye morphology, closely resembling that of the positive control group compared to other coumarin derivatives. Moreover, the group treated with S3-18 displayed a longer lifespan in comparison to the negative control group. In summary, most coumarin derivatives utilized in this study partially restored the REP, while one derivative even extended the lifespan of Drosophila. These promising findings suggest that coumarin derivatives have the potential to serve as neuroprotective drugs for the treatment of AD. Further research and development in this area may open new avenues for combating this debilitating disease.